2006
DOI: 10.1002/pbc.20923
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with health‐related quality of life in pediatric cancer survivors

Abstract: Long-term follow-up clinics for childhood cancer survivors are in a unique position to monitor HRQOL over time. Factors associated with poorer HRQOL include fatigue, ethnic minority status, a brain tumor diagnosis, and more severe late effects. Future studies need to clarify relationships between ethnicity, socioeconomic status (SES), and HRQOL in cancer survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
162
4
10

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(192 citation statements)
references
References 36 publications
16
162
4
10
Order By: Relevance
“…Eiser et al (30) reported unfavorable quality of life scores in adolescent CNS cancer patients whose treatment was completed when compared with ALL patients, most prominently observed in the physical and psychosocial subscale scores. In this study, lower quality of life scores in patients with CNS were detected, comparable to the study outcomes reported by Meeske et al (31) and Chou et al (32). This result is associated with the location of the tumor and neurocognitive changes caused by surgery and radiotherapy.…”
Section: Discussionsupporting
confidence: 91%
“…Eiser et al (30) reported unfavorable quality of life scores in adolescent CNS cancer patients whose treatment was completed when compared with ALL patients, most prominently observed in the physical and psychosocial subscale scores. In this study, lower quality of life scores in patients with CNS were detected, comparable to the study outcomes reported by Meeske et al (31) and Chou et al (32). This result is associated with the location of the tumor and neurocognitive changes caused by surgery and radiotherapy.…”
Section: Discussionsupporting
confidence: 91%
“…Mixed race/ethnicity was associated with lower Psychosocial Health Summary scores, although the basis for this association is unclear. Previous studies have reported a decreased HRQOL in children of ethnic minorities with chronic illnesses, specifically in the psychosocial realm (37)(38).…”
Section: Comparison Of Family Impact Module Results With Scores Repormentioning
confidence: 86%
“…However, other studies have found that brain tumors and treatments (like cranial radiation), which have an impact on cognitive function, were associated with long term emotional distress for survivors (26)(27)(28)(29)(30). It may be that intensity of treatment in general, and cranial radiation in very young children in particular, is related to late effects which impair function and cause emotional distress.…”
Section: Discussionmentioning
confidence: 99%